The Macroeconomic Effects of Information Asymmetry in the Capital Markets - Robert G. Kuklik (European Financial and Accounting Journal, 2012)
It is possible to say that no matter how the Efficient Market Hypothesis has been criticized and/or overhauled, a degree of the relevant data proliferation is crucial to the investor's decision making process. The information asymmetry is then a phenomenon which creates distortions in a performance of the capital market. The “pseudoeffective” market model is attempting to highlight the impact of this phenomenon on some macroeconomic variables conducive to the general economic equilibrium.
Keywords: G14; 650; Pseudoeffective market model; IS-LM framework.; Information asymmetry; Effective market equilibrium; Actual return